2009
DOI: 10.1593/neo.09230
|View full text |Cite
|
Sign up to set email alerts
|

The Plasticity of Oncogene Addiction: Implications for Targeted Therapies Directed to Receptor Tyrosine Kinases

Abstract: A common mutation of the epidermal growth factor receptor (EGFR) in glioblastoma multiforme (GBM) is an extracellular truncation known as the de2-7 EGFR (or EGFRvIII). Hepatocyte growth factor (HGF) is the ligand for the receptor tyrosine kinase (RTK) c-Met, and this signaling axis is often active in GBM. The expression of the HGF/c-Met axis or de2-7 EGFR independently enhances GBM growth and invasiveness, particularly through the phosphatidylinositol-3 kinase/pAkt pathway. Using RTK arrays, we show that expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 35 publications
2
100
0
Order By: Relevance
“…[10][11][12] Hepatocyte Growth Factor (HGF) and its receptor c-Met are both overexpressed in GBM, contributing to tumor growth invasion, angiogenesis and conferring a stem-like phenotype and poor prognosis. 10,[13][14][15][16] Although activating mutations of b-catenin have not been identified in GBM 17 , overexpression of b-catenin and other Wnt pathway components (including Fz 18 ) together with epigenetic regulation of Wnt inhibitors results in Wnt/ b-catenin activation in GBM. [19][20][21] Overexpression of the Forkhead box M1 (FoxM1) transcription factor represents a critical mechanism further contributing to b-catenin signaling in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Hepatocyte Growth Factor (HGF) and its receptor c-Met are both overexpressed in GBM, contributing to tumor growth invasion, angiogenesis and conferring a stem-like phenotype and poor prognosis. 10,[13][14][15][16] Although activating mutations of b-catenin have not been identified in GBM 17 , overexpression of b-catenin and other Wnt pathway components (including Fz 18 ) together with epigenetic regulation of Wnt inhibitors results in Wnt/ b-catenin activation in GBM. [19][20][21] Overexpression of the Forkhead box M1 (FoxM1) transcription factor represents a critical mechanism further contributing to b-catenin signaling in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have suggested that EGFR dimerization has an important role in sustaining a tumorigenic state in GBMs and evading EGFR-targeted therapies (8). Inhibitors that selectively impair dimerization of EGFRs are hence of potential interest requiring understanding of the intricacies of EGFR dimerization, specifically the interaction capacity of EGFR mutants that are relevant in the context of GBMs.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that co-expression of de2-7 EGFR and c-Met in GBM xenografts causes therapeutic resistant to single agents directed to either of these RTK. However, the combination of EGFR and c-Met inhibitors produced synergistic anti-tumor activity (Pillay et al, 2009), confirming that dual inhibition of RTKs is a valid approach in GBM. A number of other RTKs have been shown to be activated in GBM including the FGFR family, Axl, ErbB2/3/4, EphA2/7, VEGFR2 and PDGFR / (Ren et al, 2007;Pillay et al, 2009).…”
Section: Combination Of Egfr Inhibitors With Other Targeted Therapiesmentioning
confidence: 83%
“…However, the combination of EGFR and c-Met inhibitors produced synergistic anti-tumor activity (Pillay et al, 2009), confirming that dual inhibition of RTKs is a valid approach in GBM. A number of other RTKs have been shown to be activated in GBM including the FGFR family, Axl, ErbB2/3/4, EphA2/7, VEGFR2 and PDGFR / (Ren et al, 2007;Pillay et al, 2009). Given the range of potential RTKs activated in a given patient, the most effective therapeutic strategy may have to be determined by screening patient tissues for RTK mutation and/or activation (i.e.…”
Section: Combination Of Egfr Inhibitors With Other Targeted Therapiesmentioning
confidence: 83%